Moment of play: an experiment that brings playfulness to academic teaching (Revista Apotheke, 2024)
This article reports on “Playful Moments” for interdisciplinary academic teaching, based on the board game “Mental Blocks”. The game was used in Graphic Design, Civil Engineering and Environmental Engineering courses. It was therefore necessary to emphasise in this study the importance of adapting the rules of the game to suit the characteristics of each target audience, revealing that playfulness enriches the educational experience, but requires taking into account the particularities of the students. Participatory action research was used as methodological support, so that the study had a collaborative aspect. The article thus highlights the role of the teacher as a mediator between theory and practice, providing valuable insights for integrating play into teaching and inspiring future pedagogical developments.
Keywords: board games; visual pedagogies; playfulness; education; interdisciplinary